ANALISIS PENGARUH LUAS LAHAN, BESARNYA MODAL, TINGKAT PENDIDIKAN, DAN JUMLAH TENAGA KERJA TERHADAP PENDAPATAN USAHA TANI KOPI KECAMATAN DAMPIT - Arista Amanda Putri; Bahtiar Fitanto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to find out how the variables of land area, amount of capital, level of education and number of labor affect the income of coffee farmers in Dampit District. In this study using descriptive quantitative research methods with classic assumptions test and multiple linear regression analysis . The data used in this study are primary data from questionnaires and interviews with 86 respondents. This study found that the variables of land area, amount of capital and level of education partially had an influence on the income of coffee farmers in Dampit. Meanwhile, the variable number of labor has no effect on the income of coffee farmers in Dampit. From the results of this study, suggested for coffee farmers in Dampit District to further increase productivity both from physical capital or human resources in order to achieve results in the form of income effectively and efficiently.